Public assistance in patients with acute heart failure: a report from the KCHF registry - Yuji Nishimoto; Takao Kato; Takeshi Morimoto; Ryoji Taniguchi; Hidenori Yaku; Yasutaka Inuzuka; Yodo Tamaki; Erika Yamamoto; Yusuke Yoshikawa; Takeshi Kitai; Moritake Iguchi; Masashi Kato; et al. (ESC Heart Failure)
Abstract Aims There is a scarcity of data on the post‐discharge prognosis in acute heart failure (AHF) patients with a low‐income but receiving public assistance. The study sought to evaluate the differences in the clinical characteristics and outcomes between AHF patients receiving public assistance and those not receiving public assistance. Methods and results The Kyoto Congestive Heart Failure registry was a physician‐initiated, prospective, observational, multicentre cohort study enrolling 4056 consecutive patients who were hospitalized due to AHF for the first time between October 2014 and March 2016. The present study population consisted of 3728 patients who were discharged alive from the index AHF hospitalization. We divided the patients into two groups, those receiving public assistance and those not receiving public assistance. After assessing the proportional hazard assumption of public assistance as a variable, we constructed multivariable Cox proportional hazard models to estimate the risk of the public assistance group relative to the no public assistance group. There were 218 patients (5.8%) receiving public assistance and 3510 (94%) not receiving public assistance. Patients in the public assistance group were younger, more frequently had chronic coronary artery disease, previous heart failure hospitalizations, current smoking, poor medical adherence, living alone, no occupation, and a lower left ventricular ejection fraction than those in the no public assistance group. During a median follow‐up of 470 days, the cumulative 1 year incidences of all‐cause death and heart failure hospitalizations after discharge did not differ between the public assistance group and no public assistance group (13.3% vs. 17.4%, P = 0.10, and 28.3% vs. 23.8%, P = 0.25, respectively). After adjusting for the confounders, the risk of the public assistance group relative to the no public assistance group remained insignificant for all‐cause death [hazard ratio (HR), 0.97; 95% confidence interval (CI), 0.69–1.32; P = 0.84]. Even after taking into account the competing risk of all‐cause death, the adjusted risk within 180 days in the public assistance group relative to the no public assistance group remained insignificant for heart failure hospitalizations (HR, 0.93; 95% CI, 0.64–1.34; P = 0.69), while the adjusted risk beyond 180 days was significant (HR, 1.56; 95% CI, 1.07–2.29; P = 0.02). Conclusions The AHF patients receiving public assistance as compared with those not receiving public assistance had no significant excess risk for all‐cause death at 1 year after discharge or a heart failure hospitalization within 180 days after discharge, while they did have a significant excess risk for heart failure hospitalizations beyond 180 days after discharge. Clinical Trial Registration: https://clinicaltrials.gov/ct2/show/NCT02334891 (NCT02334891) and https://upload.umin.ac.jp/cgi‐open‐bin/ctr_e/ctr_view.cgi?recptno=R000017241 (UMIN000015238)